Efeito da terapia cognitiva-comportamenteal sobre as funções cognitivas e as habilidades sociais de pacientes com transtorno afetivo bipolar tipo I - Geovany Eliberto Araújo (2016)
Patients with bipolar disorder (BD) show, during the acute phase of the disease, difficulties in several cognitive domains, which lead to significant disability. Some of these changes persist even after symptom remission. In recent years there has been substantial progress in the development and assessment of psychotherapeutic interventions as add-on treatment to pharmacotherapy in severe mental disorders. The Cognitive Behavioral Therapy (CBT) is the most studied approach in BD and there is evidence that it leads to important clinical changes in the course of the disease. Clinical trials commonly have focused on symptomatic recovery, treatment adherence, reduced length and number of psychiatric hospitalizations, disease remission time, number of episodes and management of prodromal mania or depression episodes. To date, there is not a study that has used neuropsychological testing and an inventory of social skills as outcome measure after the intervention of CBT. Objective:We aimed at investigating the effects CBT on cognition and social skills of patients with BD type I in remission or depression. Methods: Thirty-five patients with BD Type I participated in the study. They were randomly divided into two groups: the first group (CBT Group, n = 17) received 20 sessions of CBT in addition to usual treatment while the second group (Control group, n = 18) received only the usual treatment. Before the CBT intervention, cognition was assessed by the Brazilian version of the Brief Assessment of Cognition in Schizophrenia-BACS and social skills were assessed by Social Skills Inventory (SSI) Del-Prette. At the end of the study, the BACS and SSI were again administered (retest). Results: Comparison of the groups (CBT and Control) over time was performed by analysis of variance (ANOVA) of two factors, Within and Between. The factors were Group and time. The data obtained from BACS and SSI show that there was a significant interaction between factors. Therefore, the groups were compared separately in Time One (T1) and Time Two (T2). On T1 assessment, the CBT group and the Control group showed no significant difference either on BACS or on SSI. On T2 assessment, the CBT group showed significantly better results than controls in both cognitive functions and social skills. Regarding BACS, there was significant differences on tests assessing executive functions (p = 0.002), attention (p = 0.018), verbal memory (p = 0.000), psychomotor speed (p = 0.010), verbal fluency (p = 0.031) and on the weighted total score (p = 0.000). Regarding SSI, the CBT group was significantly better compared to the control group (p =0.002) on total score. Conclusion: CBT as add-on treatment to pharmacotherapy of BD type 1 patients was able to significantly improve cognitive performance, as assessed by BACS, and social skills, as assessed by SSI in patients with BD type I. These results suggest that CBT can be a valuable therapeutic tool for these patients.